2007
DOI: 10.1158/1541-7786.mcr-07-0019
|View full text |Cite
|
Sign up to set email alerts
|

PEA3 Is Necessary for Optimal Epidermal Growth Factor Receptor–Stimulated Matrix Metalloproteinase Expression and Invasion of Ovarian Tumor Cells

Abstract: Elevated expression of the epidermal growth factor (EGF) receptor (EGFR) is detected in human ovarian tumors and is associated with decreased recurrence-free and overall survival. EGFR activation affects tumor progression in part by promoting tumor invasion through the induction of prometastatic matrix metalloproteinases (MMP). PEA3, an ETS family transcription factor, is elevated in advanced and metastatic ovarian cancer and regulates MMPs in various cell types, therefore, we investigated whether PEA3 is requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…The Sp1 binding site is essential for basal transcriptional activity of both MMP s as only ∼10% and ∼30% of transcription activity is observed when Sp1 at −102 on MT1-MMP in human fibrosarcoma HT-1080 and at −91 on MMP-2 in astroglioma cells is mutated respectively [38], [39]. The role of PEA3 in regulating MMP-2 and MT1-MMP expression has been demonstrated previously and inhibition of PEA3 expression using siRNA reduced MT1-MMP level by 50% in ovarian cancer cells [37], [40]. Binding of PEA3 to the MT1-MMP promoter in ovarian tumor cells is mediated through epidermal growth factor receptor (EGFR) signaling pathway [37].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The Sp1 binding site is essential for basal transcriptional activity of both MMP s as only ∼10% and ∼30% of transcription activity is observed when Sp1 at −102 on MT1-MMP in human fibrosarcoma HT-1080 and at −91 on MMP-2 in astroglioma cells is mutated respectively [38], [39]. The role of PEA3 in regulating MMP-2 and MT1-MMP expression has been demonstrated previously and inhibition of PEA3 expression using siRNA reduced MT1-MMP level by 50% in ovarian cancer cells [37], [40]. Binding of PEA3 to the MT1-MMP promoter in ovarian tumor cells is mediated through epidermal growth factor receptor (EGFR) signaling pathway [37].…”
Section: Discussionmentioning
confidence: 68%
“…The role of PEA3 in regulating MMP-2 and MT1-MMP expression has been demonstrated previously and inhibition of PEA3 expression using siRNA reduced MT1-MMP level by 50% in ovarian cancer cells [37], [40]. Binding of PEA3 to the MT1-MMP promoter in ovarian tumor cells is mediated through epidermal growth factor receptor (EGFR) signaling pathway [37]. However, activation of EGFR signaling pathway downregulated MMP-2 synthesis in SiHa cells [41].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Transcription factors specificity protein 1, hypoxia-inducible factor 2 alpha, and Krüppel-like factor 8 have been identified as potent regulators of MMP-14 expression in prostate cancer, renal cell carcinoma, and breast cancer [1113]. In ovarian cancer cells, polyomavirus enhancer activator 3 (PEA3) is able to induce MMP-14 expression via direct binding to its promoter, and knockdown of PEA3 reduces the MMP-14 levels [14]. In addition, hepatocyte nuclear factor 4 alpha exhibits oncogenic activity through directly binding to the MMP-14 promoter and facilitating its transcription in neuroblastoma [15].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, factors in the ovarian tumor microenvironment such as lysophosphatidic acid and ligands for the epidermal growth factor receptor down-regulate E-cadherin and modulate cell adhesion [99][100][101][102]. This is due, in part, to production of matrix metalloproteinases (MMPs) that cleave E-cadherin [82,[103][104][105][106], and we and others have reported that MMPs are abundant in the ascities of ovarian cancer patients [9,[107][108]. Another novel mechanism for down-regulation of E-cadherin occurs upon integrin engagement leading to MMP-9 production and E-cadherin ectodomain generation [82].…”
mentioning
confidence: 99%